(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Access to quality gynecological surgery in low- and middle-income communities has been greatly hampered by logistical and socioeconomic challenges. These challenges can be overcome through the provision of mobile laparoscopic surgery. Endoscopic surgery reduces the rate of infection, duration of hospital stay, and the need for blood transfusion, which are factors attributable to surgical disease burden due to poverty. A team comprising gynecologists, nurses, and theater technicians has been providing laparoscopic surgery to patients in low-income communities in Kiambu, Nairobi, and Meru counties in Kenya. This initiative was undertaken by pooling resources to procure basic laparoscopic equipment, a regional needs assessment for gynecological surgery, and logistical planning for outpatient clinical services. This was followed by the provision of laparoscopic surgery to patients diagnosed with various gynecological conditions. We present programmatic data of the clinical profile and outcomes of patients who benefited from the program. Results: A total of 175 women benefited from the program from January 2023 to December 2023. The most common surgery undertaken was laparoscopic hysterectomy due to symptomatic uterine fibroids. Other procedures included diagnostic hysteroscopy and laparoscopy for chronic pelvic pain. Most women were under the national health insurance fund scheme. Conclusion: The program has improved the quality of services provided and demonstrated the feasibility of mobile surgical workshops as an intervention to improve the quality of services in low-income communities.